DEVELOPMENT OF THE RESPIRATORY SYSTEM IN ADOLESCENCE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
During adolescence (17–21 years), the respiratory system undergoes significant structural and functional changes to support increasing metabolic demands and ensure lifelong respiratory health. This review examines key aspects of respiratory system maturation, including alveolarization, lung volume growth, bronchial tree development, respiratory muscle strength, and improved chest wall compliance. Sex differences are highlighted: lung development in males continues significantly during puberty, while in females, it stabilizes earlier. The clinical significance of these changes, particularly in relation to diseases like asthma and environmental factors such as air pollution, is discussed. Understanding these processes enables healthcare professionals to better address adolescent respiratory issues and promote optimal lung health in adulthood [1-12].